THE EFFECT OF INTRA-EU AND EXTRA-EU TRADE TO ECONOMIC GROWTH IN CENTRAL AND EASTERN EUROPE - Makrevska disoska, Elena (Ekonomski fakultet-Skopje, UKIM, 2019)
This paper estimates the different impact on economic growth of intra trade within EU and extra trade outside the EU for five countries from Central and Eastern Europe (Poland, Hungary, Slovenia, Slovakia and the Czech Republic). These countries have gained several benefits from their EU membership since 2004 by exploiting their huge potential. A main characteristic of the regional integration, such as the EU is the reduction/ removal of the tariff and non-tariff barriers, in order to increase trade among countries that can lead to faster economic growth. By separating the extra-EU trade flows from intra-EU trade flows and using cross-section fixed method, panel least squares for the period 2003-2017, this paper shows that trade within EU has significantly higher effect on the growth per capita, than trade with countries outside the EU in the sample CEE countries.
Keywords: intra-EU trade; extra-EU trade; Central and Eastern Europe; European Union